Behavioral nutrition and the relationship with social, physiological and emotional aspects (Research, Society and Development, 2022)
Introduction: Eating behavior is a set of cognitions and affects that govern eating actions and behaviors, in other words, human eating behavior reflects interactions between the physiological, psychological state and the external environment in which it is inserted. General objective: to elucidate the importance of behavioral nutrition in relationships with an emotional aspect, to bring a more sensitive view of the patient's condition to the consultations. Methodology: The study will be carried out with the collection of data from secondary sources, through a bibliographic survey and based on the experience lived by authors. Results and Discussion: Behavioral Nutrition proposes changes in eating behavior through self-monitoring and self-control techniques. In this perspective, it proposes to teach the individual to differentiate physical hunger from emotional hunger and suggests that eating should happen according to the sensations of hunger, appetite and satiety. Conclusion: Behavioral nutrition is not only used as a source of nutritional strategies and interventions. First, a broader approach with multiprofessional characteristics, involving a psychologist, a nutritionist, an occupational therapist and a physical education professional should be composed.